Virtual Reality as a Tool in Architectural Design Process - Pynkyawati T; Phalevi Sihombing R; W Shirley (International Conference on Engineering and Technology Development (ICETD), 2017)
Virtual reality (VR) is a technology that enables users to interact with a computersimulated environment, an actual environment that is imitated or truly an environment that exists only in imagination. The latest virtual reality environment generally presents a visual experience, displayed on a computer screen or via a stereo couple viewer, but some simulations include additional sensing information, such as sound through speakers or headphones. The emergence of virtual reality technology is pushing new changes in the field of design. Virtual reality in this case can reduce the many miss-communications that occur between the planner and the user when compared to using 2D media. The method used by discussing the phenomenon of virtual technology effects that are beneficial to the design process, by comparing the results of the real design embodied the idea of the initial idea. Where the comparison between the design results built from the designer's intuition compared with the results of virtual reality simulation test. Object of study used in the form of function of residential building to know suit owner desire which poured in the form of design and reality of field